Gadolinium-based composite phase scintillation ceramic and preparation method thereof

By introducing the second phase of Gd2O3 in the GOS scintillation ceramic to regulate its internal structure, the problem of insufficient GOS light output is solved, the light output performance and afterglow stability are significantly improved, and the detection accuracy and time resolution are improved.

CN119707494APending Publication Date: 2025-03-28QIANDONG RARE EARTH GRP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411742607.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

GOS scintillation ceramics have shortcomings in light output performance, which affects detection accuracy and time resolution.

Method used

A second phase Gd2O3 with a close density is introduced to improve scintillation performance by regulating its internal structure. The specific method includes uniformly distributing Gd2O3 in the GOS matrix, the mass fraction of the second phase is between 0.2% and 25%, and the grain size is between 0.1-1 μm.

Benefits of technology

It significantly improves the optical output performance and afterglow stability of GOS, solves the problem of insufficient optical output of GOS, and improves detection accuracy and time resolution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119707494A_ABST
    Figure CN119707494A_ABST
Patent Text Reader

Abstract

The gadolinium-based composite phase scintillation ceramic comprises a ceramic matrix and a second phase uniformly distributed in the matrix, the ceramic substrate comprises doped Gd2O2S, and the doped Gd2O2S is Pr (Phosphorus) or Tb (Thosphorus) doped Gd2O2S; the second phase comprises Gd2O3; and the mass fraction of the second phase in the composite phase scintillation ceramic is 0.2%-25%. According to the composite-phase scintillation ceramic provided by the invention, the second-phase Gd2O3 crystal phase is mainly uniformly distributed in a GOS matrix, and an experimental result shows that the Gd2O3-containing composite-phase scintillation ceramic outputs higher light and more stable afterglow under X-ray excitation compared with a scintillation ceramic without a composite phase.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of scintillation ceramics, and in particular relates to a gadolinium-based composite phase scintillation ceramic and a preparation method thereof. Background Art

[0002] Rare earth gadolinium-based scintillators are widely used in high-sensitivity radiation detectors such as X-CT, PET-CT, etc. due to their high density and excellent luminescence properties, including: yttrium gadolinium scintillator ceramics (YGO), gadolinium oxysulfide scintillator ceramics (GOS), gadolinium aluminum gallium garnet scintillator ceramics (GAGG), etc.

[0003] Among the gadolinium-based scintillators, GOS is one of the most important and widely used matrices, especially Pr-doped 3+ , Tb 3+ After plasma, afterglow is suppressed, radiation damage is reduced, and luminous efficiency is increased, making it widely used in medical CT instruments, nuclear medicine imaging, industrial non-destructive testing, high-energy physical particle detection, airport security, X-ray microscopes, "water window" soft X-ray screens and other extremely fast imaging fields. However, due to its hexagonal structure, it is optically anisotropic and has birefringence at the grain boundaries, which makes GOS unable to be prepared into transparent ceramics, so that most GOS on the market have relatively low light output, generally lower than 35000Ph / Mev, which makes GOS lower in light output performance than gadolinium-based scintillating ceramics such as YGO and GAGG, which will affect the detection accuracy and time resolution to a certain extent. Summary of the invention

[0004] Therefore, in order to solve the problem of insufficient light output of GOS, the present invention provides a new structure on the original GOS phase, introduces a second phase Gd2O3 with a similar density, and improves the scintillation performance by regulating its internal structure. To this end, the present invention provides the following technical solutions:

[0005] A gadolinium-based composite phase scintillating ceramic comprises a ceramic matrix and a second phase uniformly distributed in the matrix;

[0006] The ceramic matrix comprises doped Gd2O2S, wherein the doped Gd2O2S is Pr or Tb doped Gd2O2S;

[0007] The second phase comprises Gd2O3;

[0008] The mass fraction of the second phase in the composite phase scintillation ceramic is 0.2% to 25%.

[0009] Optionally, the mass fraction of the second phase in the composite phase scintillation ceramic is 0.5% to 20%;

[0010] Preferably, the mass fraction of the second phase in the composite phase scintillation ceramic is 4.77% to 15.15%.

[0011] Optionally, the grain size of the second phase is 0.1-1 μm.

[0012] Optionally, the doped Gd2O2S is also doped with Ce and / or F.

[0013] Optionally, the ceramic matrix is ​​made of Gd2O2S doped with Pr, Ce and F, the Pr content in the ceramic matrix is ​​400-2500ppm, the Ce content is 5-60ppm, and the F content is 0-1000ppm;

[0014] Optionally, the content of Pr in the ceramic matrix is ​​600-1100 ppm, the content of Ce is 30-60 ppm, and the content of F is 200-350 ppm.

[0015] Optionally, the ceramic matrix is ​​made of Gd2O2S doped with Tb, Ce and F, the Tb content in the ceramic matrix is ​​200-13000ppm, the Ce content is 0-100ppm, and the F content is 0-1000ppm;

[0016] Optionally, the Tb content in the ceramic matrix is ​​2500-13000 ppm, the Ce content is 30-60 ppm, and the F content is 200-350 ppm.

[0017] The preparation method of the gadolinium-based composite phase scintillating ceramic comprises the following steps:

[0018] Step 1) mixing raw materials including Gd2O2S, Gd2O3 and a doping material to obtain a mixed powder; the doping material includes at least one of a Pr source material or a Tb source material;

[0019] Step 2) Grinding, firing and annealing the mixed powder in sequence to obtain the composite phase scintillation ceramic.

[0020] Optionally, the Pr source material includes Pr6O 11 , Pr2(SO4)3, Pr(NO3)3;

[0021] Optionally, the Tb source material includes at least one of Tb4O7, Tb(NO3), and Tb2(SO4)3;

[0022] Optionally, the doping raw material further includes at least one of CeO2, Ce(NO3), CeCO3 and at least one of NaF, LiF, CaF2, MgF2;

[0023] Optionally, the purity of the Gd2O2S is not less than 99.95%, the total amount of rare earth impurities does not exceed 0.02%, wherein Nd2O3<0.005%, Sm2O3<0.01%, Y2O3<0.005%; the total amount of non-rare earth impurities does not exceed 0.01%, wherein Si<0.005%, Fe<0.001%, Na<0.005%, Al<0.002%, Zr<0.001%; ​​the Gd2O 3、 P6O 11、 The purity of Tb4O7 is >99.99%.

[0024] Optionally, the grinding includes: adding the raw material, grinding balls and solvent into a ball milling jar for ball milling;

[0025] Preferably, the ball mill is a polyurethane mill or a Teflon mill;

[0026] Preferably, the grinding balls are selected from at least one of gadolinium oxide grinding balls, GOS grinding balls, and GAGG grinding balls;

[0027] Preferably, the solvent is anhydrous ethanol and / or isopropanol.

[0028] Optionally, the sintering is performed by rapid hot pressing sintering, the heating rate of the rapid hot pressing sintering is 30-1000° C. / min, the pressure is 30-150 MPa, the sintering temperature is 1320-1650° C., and the holding time is 5-20 min;

[0029] Preferably, the rapid hot pressing sintering is to rapidly heat the product through a DC power supply; the DC current is 2000-60000A;

[0030] Preferably, the annealing is performed at a temperature 200-600° C. below the sintering temperature for 10-100 hours after sintering;

[0031] Preferably, the annealing is performed in air, argon or vacuum environment.

[0032] The present invention also proposes the application of the composite phase scintillating ceramic in medical CT instruments, nuclear medical imaging, industrial nondestructive testing, high energy physics particle detection, airport security inspection, X-ray microscope or X-ray screen.

[0033] The beneficial effects of the present invention include:

[0034] 1) The composite phase scintillating ceramic provided in the present application is mainly a second phase Gd2O3 crystal phase uniformly distributed in a GOS matrix. Experimental results show that the scintillating ceramic containing the Gd2O3 composite phase has a higher light output and a more stable afterglow under X-ray excitation than the scintillating ceramic without the composite phase;

[0035] 2) The composite phase scintillation ceramics provided in this application effectively solve the problem of multiple radiation instability of GOS afterglow;

[0036] 3) The preparation method of the composite phase scintillating ceramic provided in the present application adopts rapid hot pressing sintering combined with high temperature annealing to obtain a ceramic scintillator mixed with GOS and Gd2O3. The preparation method is simple and easy to implement on a large scale. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0038] Figure 1 is a photo of a composite phase scintillation ceramic in an embodiment of the present invention; wherein Figure 1 a is the sample of Example 1, Figure 1 b is the sample of Example 4.

[0039] Figure 2 XRD diagram of the composite phase scintillating ceramic in the embodiment of the present invention;

[0040] Figure 3 SEM image of the composite phase scintillating ceramic in the embodiment of the present invention;

[0041] Figure 4 Afterglow spectrum of the composite phase scintillating ceramic in the embodiment of the present invention under X-ray excitation;

[0042] Figure 5 Light output spectrum of the composite phase scintillating ceramic in an embodiment of the present invention under X-ray excitation. DETAILED DESCRIPTION

[0043] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0044] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0045] Example 1

[0046] Weigh 189.65g of Gd2O2S powder with a purity of 99.99%, 0.01g of Ce2(CO3)3, and 0.01g of Pr6O 11 0.15g, Gd2O3 10g, LiF0.2g, add 200ml of anhydrous ethanol, 200g of GAGG grinding ball, ball mill at 420 speed / min for 3 hours, dry at 120℃ for 8 hours to obtain a precursor, put it into a 55*55mm graphite mold, raise the temperature to 715℃ at a rate of 100℃ / min, pressurize to 15.4T, keep at 1500℃ for 10min, anneal in air at 1000℃ for 10h, and obtain a composite ceramic with 95.23% GOS phase and 4.77% Gd2O3 phase, see Figure 1 a.

[0047] Example 2

[0048] Weigh 179.53g of 99.95% purity Gd2O2S powder, 0.025g of Ce(NO3), 0.43g of Pr2(SO4)3, 20g of Gd2O3, and 0.2g of NaF, add 100ml of anhydrous ethanol, 100ml of isopropanol, and 200g of GOS balls, ball mill at 300 rpm for 3 hours, and dry at 120℃ for 8 hours to obtain a precursor, put it into a 55*55mm graphite mold, raise the temperature to 715℃ at a rate of 50℃ / min, apply pressure to 46.2T, then increase the current to 9500A, keep warm at 1400℃ for 20min, and anneal in air at 900℃ for 50h to obtain a composite ceramic with 92.59% GOS phase and 7.4% Gd2O3 phase.

[0049] Example 3

[0050] Weigh 174.64g of Gd2O2S powder with a purity of 99.99%, 0.0075g of CeO2, and 0.0075g of Pr6O 11 0.15g, Gd2O325g, MgF20.2g, add 100ml anhydrous ethanol, 100ml isopropanol, 200g GOS ball, 300 rpm ball milling for 1 hour, 120 ℃ drying for 8 hours to get a precursor, put it into a 55*55mm graphite mold, raise the temperature to 715 ℃ at a rate of 50 ℃ / min, pressurize to 15.4T, then increase the current to 10000A, keep warm at 1450 ℃ for 20min, anneal in air at 900 ℃ for 50h to obtain a composite ceramic with 90.9% GOS phase and 9.1% Gd2O3 phase.

[0051] Example 4

[0052] Weigh 224.08g of 99.99% pure Gd2O2S powder, 0.015g of Ce2(CO3)3, 0.75g of Tb4O7, 25g of Gd2O3, and 0.15g of MgF2, add 125ml of anhydrous ethanol, 125ml of pure water, and 200g of GAGG balls, ball mill at 300 rpm for 3 hours, and dry at 120℃ for 8 hours to obtain a precursor, which is loaded into a Φ80mm mold, raised to 715℃ at a rate of 30℃ / min, pressurized to 25.6T, then the current is raised to 12000A, kept at 1600℃ for 20min, and annealed in air at 1000℃ for 50h to obtain a composite ceramic with a GOS phase of 90.9% and a Gd2O3 phase of 9.1%, see Figure 1 b.

[0053] Example 5

[0054] Weigh 224.66g of 99.99% pure Gd2O2S powder, 30.02g of Ce2(CO3), 5g of Tb2(SO4)3·8H2O, 20g of Gd2O3, and 0.25g of LiF, add 100ml of anhydrous ethanol, 100ml of pure water, and 200g of GAGG balls, ball mill at 300 rpm for 3 hours, and dry at 120°C for 8 hours to obtain a precursor, which is loaded into a Φ80mm mold, raised to 715°C at a rate of 30°C / min, pressurized to 25.6T, then the current is raised to 12000A, kept at 1600°C for 20min, and annealed in air at 950°C for 100h to obtain a composite ceramic with 92.59% GOS phase and 7.4% Gd2O3 phase.

[0055] Example 6

[0056] Weigh 201.56g of 99.99% purity Gd2O2S powder, 0.015g of Ce2(CO3)3, 3.13g of Tb(NO), 45g of Gd2O3, and 0.25g of LiF, add 100ml of anhydrous ethanol, 100ml of pure water, and 200g of GAGG balls, ball mill at 300 rpm for 3 hours, and dry at 120℃ for 8 hours to obtain a precursor, put it into a Φ80mm mold, raise the temperature to 715℃ at a rate of 30℃ / min, apply pressure to 25.6T, then increase the current to 12000A, keep warm at 1550℃ for 15min, anneal in air at 900℃ for 100h, and obtain a composite ceramic with 84.75% GOS phase and 15.15% Gd2O3 phase.

[0057] Example 7

[0058] Weigh 208.3g of 99.99% pure Gd2O2S powder, 3.75g of Tb4O7, and 40g of Gd2O3, add 125ml of anhydrous ethanol, 125ml of pure water, and 250g of GOS balls, ball mill at 500 rpm for 3 hours, and dry at 120℃ for 8 hours to obtain a precursor, load it into a Φ80mm mold, raise the temperature to 715℃ at a rate of 35℃ / min, apply pressure to 25.6T, then increase the current to 13500A, keep at 1650℃ for 20min, and anneal in vacuum at 1100℃ for 10h to obtain a composite ceramic with 85.62% GOS phase and 13.38% Gd2O3 phase.

[0059] Example 8

[0060] Weigh 245.88g of 99.99% pure Gd2O2S powder, 2.7g of Tb4O7, 0.022g of CeCO3, 1.27g of Gd2O3, and 0.12g of CaF2, add 120ml of anhydrous ethanol, 120ml of pure water, and 240g of GOS balls, ball mill at 500 rpm for 3 hours, and dry at 120℃ for 8 hours to obtain a precursor, which is loaded into a 55*55mm carbon-carbon mold, and the temperature is raised to 715℃ at a rate of 55℃ / min. The pressure is increased to 30.4T, and then the current is increased to 8500A, kept at 1500℃ for 20min, and annealed in vacuum at 1000℃ for 10h to obtain a composite ceramic with 99.5% GOS phase and 0.5% Gd2O3 phase.

[0061] Comparative Example 1

[0062] Weigh 199.63g of Gd2O2S powder with a purity of 99.99%, 0.02g of CeCO3, and 0.02g of Pr6O 11 0.15g, LiF 0.2g, add anhydrous ethanol 200ml, GAGG grinding ball 200g, ball mill at 420 speed / min for 3 hours, dry at 120℃ for 8 hours to get a precursor, put it into a 55*55mm graphite mold, raise the temperature to 715℃ at a rate of 100℃ / min, pressurize to 15.4T, keep warm at 1500℃ for 10min, anneal in air at 1000℃ for 10h to obtain a composite ceramic with 100% GOS phase and 0% Gd2O3 phase.

[0063] Comparative Example 2

[0064] Weigh 248.97g of 99.99% pure Gd2O2S powder, 0.035g of CeCO3, 0.75g of Tb4O7, and 0.25g of LiF, add 125ml of anhydrous ethanol, 125ml of isopropanol, and 250g of GOS balls, ball mill at 300 rpm for 1 hour, and dry at 120℃ for 8 hours to obtain a precursor, which is loaded into a 55*55mm graphite mold, raised to 715℃ at a rate of 50℃ / min, pressurized to 15.4T, then the current is increased to 10000A, kept at 1450℃ for 20min, and annealed in air at 900℃ for 50h to obtain a composite ceramic with 100% GOS phase and 0% Gd2O3 phase.

[0065] Comparative Example 3

[0066] Weigh 173.99g of 99.99% pure Gd2O2S powder, 0.015g of CeCO3, 0.6g of Tb4O7, 75g of Gd2O3, and 0.25g of LiF, add 100ml of anhydrous isopropanol, 100ml of pure water, and 200g of GAGG balls, ball mill at 300 rpm for 3 hours, and dry at 120℃ for 8 hours to obtain a precursor, put it into a 80*80mm mold, raise the temperature to 715℃ at a rate of 30℃ / min, apply pressure to 32.6T, then increase the current to 15000A, keep warm at 1550℃ for 15min, anneal in air at 900℃ for 75h, and obtain a composite ceramic with 76.92% GOS phase and 23% Gd2O3 phase.

[0067] Comparative Example 4

[0068] Weigh 179.55g of 99.99% pure Gd2O2S powder, 0.050g of CeCO3, and 0.050g of Pr6O 11 0.15g, Gd2O3 70g, LiF0.25g, add 100ml anhydrous isopropanol, 100ml pure water, 200g GOS ball, ball mill at 300 rpm for 3 hours, dry at 120℃ for 8 hours to get a precursor, put it into a Φ50mm mold, raise the temperature to 715℃ at a rate of 80℃ / min, pressurize at 30T, then increase the current to 8000A, keep warm at 1350℃ for 20min, anneal in air at 900℃ for 50h to obtain a composite ceramic with 78.13% GOS phase and 21.86% Gd2O3 phase.

[0069] Test example:

[0070] XRD tests were performed on the composite phase scintillating ceramics in Example 1 (GOS-1), Example 4 (GOS-3), and Example 8 (GOS-2). The test results showed that the composite phase scintillating ceramics with added Gd2O3 all showed diffraction peaks of the matrix and the second phase. Figure 2 .

[0071] Taking the sample in Example 4 as an example, Figure 3 The SEM image is Figure 3 It can be seen that the matrix of the gadolinium-based composite scintillating ceramic is composed of a GOS phase with a size of 50 μm, and a second phase precipitated on its surface has a grain size of 0.2 μm.

[0072] Take the sample in Example 4 as an example, the product thickness is 3.0mm, and the afterglow and light output are tested (test conditions: X-ray machine voltage 90kv, current 1.2mA), the results are shown in Figure 4 and Figure 5 .

[0073] The data of various examples and comparative examples, namely 20 ms persistence and light output, are given in Table 1.

[0074] Table 1

[0075]

[0076] By comparing the above embodiments and comparative examples, it can be seen that the gadolinium-based composite phase scintillating ceramics in the present invention can obtain higher light output and more stable afterglow, and the performance is significantly improved.

[0077] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A gadolinium-based composite phase scintillating ceramic, characterized in that: It includes a ceramic matrix and a second phase uniformly distributed in the matrix; The ceramic matrix comprises doped Gd2O2S, wherein the doped Gd2O2S is Pr or Tb doped Gd2O2S; The second phase comprises Gd2O3; The mass fraction of the second phase in the composite phase scintillation ceramic is 0.2% to 25%.

2. The gadolinium-based composite phase scintillating ceramic according to claim 1, characterized in that: The mass fraction of the second phase in the composite phase scintillation ceramic is 0.5% to 20%; Preferably, the mass fraction of the second phase in the composite phase scintillation ceramic is 4.77% to 15.15%.

3. The gadolinium-based composite phase scintillating ceramic according to claim 1, characterized in that: The grain size of the second phase is 0.1-1 μm.

4. The gadolinium-based composite phase scintillating ceramic according to claim 1, characterized in that: The doped Gd2O2S is also doped with Ce and / or F.

5. The gadolinium-based composite phase scintillating ceramic according to claim 1, characterized in that: The ceramic matrix is ​​made of Gd2O2S doped with Pr, Ce and F, wherein the content of Pr in the ceramic matrix is ​​400-2500ppm, the content of Ce is 5-60ppm, and the content of F is 0-1000ppm; Preferably, the content of Pr in the ceramic matrix is ​​600-1100 ppm, the content of Ce is 30-60 ppm, and the content of F is 200-350 ppm.

6. The gadolinium-based composite phase scintillating ceramic according to claim 1, characterized in that: The ceramic matrix is ​​made of Gd2O2S doped with Tb, Ce and F, the content of Tb in the ceramic matrix is ​​200-13000ppm, the content of Ce is 0-100ppm, and the content of F is 0-1000ppm; Preferably, the content of Tb in the ceramic matrix is ​​2500-13000 ppm, the content of Ce is 30-60 ppm, and the content of F is 200-350 ppm.

7. The method for preparing the gadolinium-based composite phase scintillating ceramic according to any one of claims 1 to 6, characterized in that: The steps include: Step 1) mixing raw materials including Gd2O2S, Gd2O3 and a doping material to obtain a mixed powder; the doping material includes at least one of a Pr source material or a Tb source material; Step 2) Grinding, firing and annealing the mixed powder in sequence to obtain the composite phase scintillation ceramic.

8. The method for preparing the gadolinium-based composite phase scintillating ceramic according to claim 7, characterized in that: The Pr source material includes Pr6O 11 , Pr2(SO4)3, Pr(NO3)3; The Tb source material includes at least one of Tb4O7, Tb(NO3), and Tb2(SO4)3; Preferably, the doping raw material further includes at least one of CeO2, Ce(NO3), CeCO3 and at least one of NaF, LiF, CaF2, MgF2; Preferably, the purity of the Gd2O2S is not less than 99.95%, the total amount of rare earth impurities does not exceed 0.02%, wherein Nd2O3<0.005%, Sm2O3<0.01%, Y2O3<0.005%; the total amount of non-rare earth impurities does not exceed 0.01%, wherein Si<0.005%, Fe<0.001%, Na<0.005%, Al<0.002%, Zr<0.001%; ​​the Gd2O 3、 P6O 11、 The purity of Tb4O7 is >99.99%.

9. The method for preparing the gadolinium-based composite phase scintillating ceramic according to claim 7, characterized in that: The grinding comprises: adding the raw material, grinding balls and solvent into a ball mill, wherein the ratio of raw material: grinding balls: solvent is 1:1:1; Preferably, the ball mill is a polyurethane mill or a Teflon mill; Preferably, the grinding balls are selected from at least one of gadolinium oxide grinding balls, GOS grinding balls, and GAGG grinding balls.

10. The method for preparing the gadolinium-based composite phase scintillating ceramic according to claim 7, characterized in that: The sintering adopts rapid hot pressing sintering, the heating rate of the rapid hot pressing sintering is 30-1000°C / min, the pressure is 35-150Mpa, the sintering temperature is 1320-1650°C, and the holding time is 5-20min; Preferably, the annealing is to perform heat treatment for 10-100h at a temperature 200-600°C lower than the sintering temperature after sintering; Preferably, the annealing is performed in air, argon or vacuum environment.

11. Use of the gadolinium-based composite phase scintillating ceramic according to any one of claims 1 to 6 in medical CT instruments, nuclear medicine imaging, industrial nondestructive testing, high-energy physics particle detection, airport security, X-ray microscopes or X-ray screens.